Critical questions in sustainability and hospitality - Day, Jonathon G.; Kuokkanen, Henri; Legrand, Willy (London Routledge/Taylor & Francis Group, 2023)
"Informed by the scholarly and practical viewpoints of a myriad of internationally-recognised experts, this engaging and timely volume poses a set of pertinent questions that cover critical and contemporary sustainability issues in hospitality and tourism and proposes actionable solutions. This book is an essential reading for students and academics in the field of hospitality and tourism management, as well as industry professionals searching for answers to challenges they face in enacting sustainability in their business"--
Includes bibliographical references and index.
Keywords: Social responsibility of business; Hospitality industry -- Environmental aspects; Hospitality industry -- Management; Sustainable tourism -- Management